Willingness as a mediator of the effects of personality on alcohol-related consequences between the first and second years of college: A longitudinal prospective study. (February 2019) - Trager, Bradley M.; Mallett, Kimberly A.; Turrisi, Rob; Sell, Nichole M.; Hultgren, Brittney A.
Abstract: The present study used a prospective longitudinal design to examine whether willingness to experience negative alcohol-related consequences mediated the effects of personality on consequences (e.g., blacking out, getting into a fight, and regretted sex). Students (N = 2024) were assessed at three time points: fall semester of the students' first year in college (baseline), 6-months post-baseline, and one-year post-baseline. Personality constructs were assessed at baseline (i.e., impulsivity, sensation seeking, self-regulation), willingness to experience negative alcohol-related consequences was assessed at baseline and 6-months, and negative alcohol-related consequences were examined at baseline and one-year post-baseline. A structural path model was used to examine if willingness mediated the effects of personality on consequences. Baseline drinking was included as a covariate in the model. Results demonstrated willingness to experience consequences significantly mediated the effects of impulsivity, sensation seeking, and self-regulation on consequences. Findings from this study support the idea that consequence-specific cognitions, such as willingness, can explain changes in consequences associated with personality. This suggests that intervention efforts aimed at reducing negative alcohol-related consequences could benefit from the inclusion of consequence-specific cognitions, personality (e.g., impulsivity, sensation seeking, and self-regulation), and drinking. Highlights: Higher self-regulation predicted lower willingness to experience consequences . Impulsivity and sensation seeking were positively associated with willingness. Willingness was negatively associated with alcohol-related consequences . Willingness mediated the effects of all three personality constructs on consequences.